Application of Restorative Justice on Criminal Acts of Narcotics Abuse Performed By Children Through Diversion In Denpasar - Yunita Parisman; A.A.A.N. Tini Rusmini Gorda (IHSA Institute, 2022)
Drug abuse is a crime and a violation that threatens safety. Narcotics abusers are currently not only carried out by adults, even children are involved in it. Children as perpetrators of narcotics crimes must be given protection by prioritizing the fulfillment of their rights and preventing children from the criminal justice process which will stigmatize or label children, including preventing children from being punished. imprisonment in Indonesia has Law no. 11 of 2012 concerning the Juvenile Criminal Justice System, which was issued with the aim of realizing a court that truly guarantees the best interests of children in conflict with the law. especially children in conflict with the law In the Juvenile Criminal Justice System Act, there is a principle of restorative justice which aims to keep children away from the judicial process and keep away criminal sanctions for children in conflict with the law. But in the application of the law it still has a negative impact on the future of children